1994
DOI: 10.1093/nar/22.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of serine and leucine tRNAs in an asporogenic yeastCandida cylindraceaand evolutionary implications of genes for tRNASerCAG responsible for translation of a non-universal genetic code

Abstract: Five serine and three leucine isoaceptor tRNAs were purified from the asporogenic yeast Candida cylindracea, in which codon CUG is translated as serine instead of leucine, and their primary structures were determined. From the wobble hypothesis, it was assumed that one of the tRNA(Leu) species (Leu1), with the anticodon CmAA, corresponded to the UUG leucine codon, and that the remaining two leucine tRNAs (Leu2 and Leu3), with the same IAG anticodon sequence would decode the CUU, CUC and CUA codons as leucine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Similar observations were previously made in several Candida species [13,14] and Debaryomyces hansenii [15]. Unfortunately, we have not been able to identify the corresponding tRNA gene suggesting that it is present at a low copy number.…”
Section: Trnassupporting
confidence: 86%
“…Similar observations were previously made in several Candida species [13,14] and Debaryomyces hansenii [15]. Unfortunately, we have not been able to identify the corresponding tRNA gene suggesting that it is present at a low copy number.…”
Section: Trnassupporting
confidence: 86%
“…Purified tRNA Tyr accepted at least 1.4 nmol of tyrosine/A 260 unit, determined in an aminoacylation assay described elsewhere (11). To isolate tRNA Ser acceptors, the tRNA was serylated using pure seryl-tRNA synthetase, derivatized by naphthoxyacetylation (36), and purified by chromatography on a benzoylated DEAE-cellulose column (37). The aliquots from the chromatography fractions were subjected to electrophoresis on a 8% polyacrylamide gel containing 8 M urea.…”
Section: Methodsmentioning
confidence: 99%
“…In order to demonstrate the validity of this method, we selected a serine tRNA having the anticodon CAG (tRNASerCAG), corresponding to the universal leucine codon CUG, from Candida cylindracea [15,16]. We have already reported that the universal leucine codon CUG is read as serine in several Candida species by a specific serine tRNA corresponding to the codon CUG (tRNASerCAG) [17,18], following an experiment showing that the codon CUG can in fact be translated as serine in an in vitro translation with this serine tRNA using synthetic mRNA containing the in-frame CUG codons [15,16]. Here, we attempted to analyze the aminoacylated form of this serine tRNA in the cell to ensure that the tRNA is also charged with serine even in vivo.…”
Section: Introductionmentioning
confidence: 99%